GAMBARAN BAKTERI DAN SENSITIVITAS ANTIBIOTIK PADA PASIEN STROKE DENGAN SEPSIS DI RUANG NEUROLOGI RSUP HAJI ADAM MALIK MEDAN - Etiya Ekayana,* Aida Fithrie,* Irina Kemala Nasution* (NEURONA, 2019)
INTRODUCTION STROKE PATIENTS ARE AT HIGH RISK OF SEPSIS BECAUSE OF THE IMMUNESUPPRESSIVE EFFECT OF CEREBRAL DAMAGE AND THE IMMOBILIZATION DUE TO NEUROLOGICAL DEFICIT THE CHOICE OF EMPIRIC ANTIBIOTICS FOR SEPSIS DEPENDS ON EPIDEMIOLOGY DATA OF THE BACTERIAL PATTERN AND ANTIBIOTICS SENSITIVITY